Applying an Appropriate Mathematical Model to Evaluate Suppliers in Supply Chain using Mikhailov Method - Ahmad Tavakoli; Hossein Didehkhani; Amir Kariznoee; Hossein Sadeghpoor (چشم‌انداز مدیریت صنعتی, 2012)
One area of importance in Supply Chain Management Which has always been targeted by researchers is evaluating and selecting the suppliers. This article employs a mixed model of Fuzzy analytical hierarchy process and Fuzzy mathematical planning to assess and hand-pick suppliers of a car parts manufacturer. This model consists of two steps. In the first step, suppliers' total utility has been measured considering 13 factors, Fuzzy analytical hierarchy process has been applied in this stage. In the second step using a Fuzzy mathematical planning model we recognized suppliers' optimum purchasing basket. The algorithm used in analytical hierarchy process is Mikhailov algorithm which presents various advantages namely compatibility index, presenting a definite weight vector, and applicable with incomplete matrix. The result of the article show that applying this model will enable decision makers-merging quantitative and non quantitative criteria-not only to improve the quality of their decisions but also to be well assured of their course of actions.